Attitude and Behaviour of Society towards Transport Carbon Emission Pollution in Sintok, Kedah - Badlishah, Shahrizal; Mustaffa, Abaidullah; Fitriani Usman, Nora; Rahim, Fatin (International Journal of Psychosocial Rehabilitation, 2020)
Carbon emission pollution and its effect on society have attracted international attention due to environmental, social, and economic problems. However, it appears that society’s attitude and behaviour are still unclear about the effects of carbon emissions from transport as atmospheric pollutants. The purpose of this research is to study society’s behaviour using the Tripartite Model of Attitude (TMA) as the underpinning theory towards transportation with low carbon emissions in Sintok, Kedah. A quantitative approach has been used by using self-administered survey questionnaires adopting a 5-point Likert scale with validated multi-item scale measurements. A quota sampling technique was used to sample 192 respondents from society in Sintok, Kedah. Dependent variable is behaviour with a single dimension. The independent variables are three components of attitude, namely cognition, affection, and conation. Multiple regression has been used for data analysis and hypothesis testing. This research explored the behavior of society using attitude sub-dimensions towards transportation with low carbon emissions in Sintok, the state of Kedah, Malaysia. The main finding is that cognitive a sub-dimension of attitude is not supported. However, affective and conative are supported.